Characterizations on microencapsulated sunflower oil as self-healing agent using In situ polymerization method - BAHAROM, Z.; Idris, M.I.; Lee, T.C.; SYED ABU BAKAR, S.A.; Abdullah, H.Z. (2020)
This paper emphasizes the characterization on the microencapsulation of sunflower oil as self-healing agent. In-situ polymerization method mainly implicates in the microencapsulation process. The analysis of microencapsulated sunflower oil via prominent characterization of yield of microcapsules, microcapsules characteristics and Fourier Transmission Infa-Red Spectroscopy (FTIR). The prime optimization used was reaction time of microencapsulation process in the ranges of 2, 3 and 4 h. The higher reaction time of microencapsulation process resulted in a higher yield of microcapsules. The yield of microcapsules increases from 46 to 53% respectively by the increasing of reaction time from 2 to 4 h. The surface morphology study associating the diameter of microcapsules measured to analyse the prepared microcapsules. It was indicated that microcapsules were round in shape with smooth micro-surfaces. It was discovered that the diameter of microcapsules during microencapsulation process after 4 h reaction time was in average of 70.53 μm. This size was measured before filtering the microcapsules with solvent and dried in vacuum oven. Apparently, after filtering and drying stage, the diameter of microcapsules specifically identified under Field Emission Scanning Electron Microscopy (FESEM) showing the size of 2.33 μm may be due to the removing the suspended oil surrounded the microcapsules. Sunflower oil as core content and urea formaldehyde (UF) as shell of microcapsules demonstrated the proven chemical properties on characterization by FTIR with the stretching peak of 1537.99 - 1538.90 cm-1 (-H in -CH2), 1235.49 - 1238.77 cm-1 (C-O-C Vibrations at Ester) and 1017.65 - 1034.11 cm-1 (C-OH Stretching Vibrations). It was showed that sunflower oil can be considered as an alternative nature resource for self-healing agent in microencapsulation process. The characterization of microencapsulated sunflower oil using in-situ polymerization method showed that sunflower oil was viable self-healing agent to be encapsulated and incorporated in metal coating.